Nigeria’s foreign reserves and the challenges of development, 1960–2010 (2018)
Since independence in 1960, the Nigerian state has struggled to earn for itself a respectable position globally. Scholars of various disciplines such as economics, political science, sociology and history through their works, have examined those resources that enhance the country’s economic potentials. Resources such as cocoa, groundnut, palm oil and palm kernel which served as the country’s export potentials as well as foreign exchange earnings before crude oil export became the kernel of Nigeria’s foreign exchange earnings in the 1970s are typical examples of the country’s exports that had boosted its foreign reserves in the past. Similarly, scholars of various disciplines since crude oil became the backbone of the country’s economy have made attempts at charting new approaches through which the country’s exports can be enhanced vis-à-vis its foreign reserves. These include effective and functional refineries, maximum exploitation f other items such as gas as embedded in the country’s crude exports, deregulation of both upstream and downstream sectors of the oil industry as well as the exploitation of non-oil sectors for exports. However, adequate and comprehensive intellectual attention has not been paid to the connection between the vicissitudes and diversities of Nigeria’s foreign reserves and the country’s economic development. It is against this backdrop that this paper interrogates the nature of Nigeria’s economic development from the perspective of its foreign reserves. The paper argues in its conclusion that Nigeria’s development prospects and challenges are tied to the management of its foreign reserves by the successive administrations since 1960.